The Things That Mark an Apostle - Jaap Doedens (The Biblical Annals, 2021)
The Acts of the Apostles describes – sometimes in rather colorful details – signs and wonders wrought by the apostle Paul. Can this portrait of the apostle be corroborated based on his own letters? Or do we have to conclude that contemporaries of the apostle paint a more or less hagiographic picture of Paul’s miraculous activities? What is the place of miracles surrounding Paul and wrought by him within the whole of his life and mission?  A survey of Paul’s letters allows us to get a view of how the apostle sees the function of signs, wonders, and mighty works within the dynamics of the proclamation of the gospel. Viewed in this way, the possible difference between information based upon Paul’s own communication and that of his contemporaries about him appears to decrease. A clearer picture of the part miracles play within the whole of Paul’s mission may also help to rethink modern and post-modern worldviews from a biblical perspective.